Perceptions and attitudes influencing the management of solid waste in the Kumasi Metropolis, Ghana - Neizer, Amos Alfred (2015)
A thesis submitted to the Department of Sociology and Social Work, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of Master of Arts in Sociology.